Unpublished epistolary exchanges between Deodoro Roca and Octavio Pinto - Gaiteri, Esmeralda (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: Analyze unpublished letters from Octavio Pinto addressed to Deodoro Roca during the year 1917. Originality: To reveal previously unknown correspondence from a personality as important as Octavio Pinto to Deodoro Roca. Both are key figures who contributed to the artistic and political fields during the first half of the 20th century in Argentina. Method: it is a qualitative research. Through hermeneutics, content analysis of the letters was carried out. Strategies/ Data Collection: the letters were the source of information to understand  ideological matrices on private or everyday aspects of important figures such as Octavio Pinto and Deodoro Roca. Conclusions: The main conclusion after the analysis is that the letters confirm the friendly bond between Pinto and Roca and their shared concerns about art and education. Both spotted a different direction regarding how nationalism in Argentine society had been thought.